Bioethics in Genetics: between science and art - Ana Rita Soares; Ana Sofia Carvalho (Instituto Politécnico de Viseu, 2023)
Medical Genetics is a transversal and multidisciplinary medical speciality whose activity encompasses, in a general and simplistic perspective, the diagnosis of rare genetic diseases and genetic counselling of hereditary pathologies. Genetic information is, more than medical information, health information and it has implications not only for the self but also for family members. Although this medical specialization deals with risks and probabilities based on exact sciences and rigorous laboratory methodology, it also keeps challenging professionals to think ethically in different daily situations. Even in cases where the law is specific and quite rigorous on how to deal with the problem, it can be challenging to know which is the most ethical conduct in this rarity world. Henceforth, some examples will be given to make us think about how genetics can be a science art with certainties and queries.